A Low-Serum Culture System for Prolonged in Vitro Toxicology Experiments on a Macrophage System - Dalzon, Bastien; Torres, Anaelle; Devcic, Julie; Fenel, Daphna; Sergent, Jacques-Aurélien; Rabilloud, Thierry (Frontiers in Toxicology, 2021)
Immunotoxicology sensu lato comprises not only toxicity toward immune cells, but also biological reactions from immune cells exposed to toxicants, reactions that may have deleterious effects at the organismal level. Within this wide frame, a specific case of interest is represented by the response of macrophages to particulate materials, with the epitome examples of asbestos and crystalline silica. For such toxicants that are both persistent and often encountered in an occupational setting, i.e. at low but repeated doses, there is a need for in vitro systems that can take into account these two parameters. Currently, most in vitro systems are used in an acute exposure mode, i.e. with a single dose and a readout made shortly if not immediately after exposure. We describe here how adequate changes of the culture methods applied to the murine macrophage cell line J774A.1 enable longer periods of culture (several days), which represents a first opportunity to address the persistence and dose-rate issues. To respond to this, the protocol uses a reduction in the concentration of the animal serum used for cell culture, as well as a switch from fetal to adult serum, which is less rich in proliferation factors. By doing so, we have considerably reduced cell proliferation, which is a problem with cell lines when they are supposed to represent slowly-dividing cells such as resident macrophages. We also succeeded in maintaining the differentiated functions of macrophages, such as phagocytosis or inflammatory responses, over the whole culture period. Furthermore, the presence of serum, even at low concentrations, provides excellent cell viability and keeps the presence of a protein corona on particulate materials, a feature that is known to strongly modulate their effects on cells and is lost in serum-free culture. Besides data showing the impact of these conditions on macrophages cell line cultures, illustrative examples are shown on silica- and cobalt-based pigments.